2022
DOI: 10.1021/acsanm.2c01899
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Energy Transfer in Organic Nanoparticles Based on Small-Molecule Ionic Isolation Lattices for UV Light Harvesting

Abstract: Fluorescent nanoparticles based on organic dyes are promising materials for bioimaging applications. Recently, ultrabright fluorescent nanoparticles with orange emission were obtained by hierarchical coassembly of a cationic rhodamine dye with cyanostar anion-receptor to produce small-molecule ionic isolation lattices (SMILES). The cyanostar anion-complexes provides spatial and electronic isolation of the rhodamine dye prohibiting aggregation quenching. Cyanostar also constitutes a UV excitation antenna system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Simply adding the anion-binding macrocycle cyanostar (CS) 44 to cationic fluorophores induced predictable packing of the dyes into small-molecule ionic isolation lattices (SMILES, Figure 1A), where cationic fluorophores (green) are efficiently isolated from each other by the large disc-shaped anion complexes formed between anions (orange) and 2 equiv of CS (gray, Figure 1B), as sketched in Figure 1. 45,46 The SMILES concept has been demonstrated for a range of prevalent dye classes in both thin films and crystals, 45 as well as in nanoparticles, 47,48 yielding both very high brightness and high dye density in the solids (up to ∼0.5 M, or one dye per 3.5 nm 3 ).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simply adding the anion-binding macrocycle cyanostar (CS) 44 to cationic fluorophores induced predictable packing of the dyes into small-molecule ionic isolation lattices (SMILES, Figure 1A), where cationic fluorophores (green) are efficiently isolated from each other by the large disc-shaped anion complexes formed between anions (orange) and 2 equiv of CS (gray, Figure 1B), as sketched in Figure 1. 45,46 The SMILES concept has been demonstrated for a range of prevalent dye classes in both thin films and crystals, 45 as well as in nanoparticles, 47,48 yielding both very high brightness and high dye density in the solids (up to ∼0.5 M, or one dye per 3.5 nm 3 ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Anion-binding receptors offer a supramolecular approach to modify the size, shape, and properties of anions and thus packing of molecular salts. , Taking this direction, we recently introduced a new and simple method to produce bright fluorescent solid-state materials from conventional organic dyes. Simply adding the anion-binding macrocycle cyanostar (CS) to cationic fluorophores induced predictable packing of the dyes into small-molecule ionic isolation lattices (SMILES, Figure A), where cationic fluorophores (green) are efficiently isolated from each other by the large disc-shaped anion complexes formed between anions (orange) and 2 equiv of CS (gray, Figure B), as sketched in Figure . , The SMILES concept has been demonstrated for a range of prevalent dye classes in both thin films and crystals, as well as in nanoparticles, , yielding both very high brightness and high dye density in the solids (up to ∼0.5 M, or one dye per 3.5 nm 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Upon tuning, they found that the energy-transfer efficiency could be increased by 100%. 3 Liu et al studied an interesting phenomenon of ligand-induced transformation of CsPbBr 3 nanocrystals to nanowires for applications as X-ray photodetectors, where the photodetectors fabricated using the obtained CsPbBr 3 nanowires displayed enhanced photocurrents. 4 In another work, Beton and coauthors achieved submolecular resolution imaging based on P 3 HT:PCBM films, showing a promising application potential in organic photovoltaic devices.…”
Section: Sustainabilitymentioning
confidence: 99%
“…Laursen et al quantitatively investigated the energy transfer in small-molecule self-assembled nanoparticles for harvesting UV light. Upon tuning, they found that the energy-transfer efficiency could be increased by 100% . Liu et al studied an interesting phenomenon of ligand-induced transformation of CsPbBr 3 nanocrystals to nanowires for applications as X-ray photodetectors, where the photodetectors fabricated using the obtained CsPbBr 3 nanowires displayed enhanced photocurrents .…”
Section: Nanosystems For Energy and Sustainabilitymentioning
confidence: 99%
“…Simply adding the anion-binding macrocycle cyanostar (CS) 43 to cationic fluorophores induced predictable packing of the dyes into small-molecule ionic isolation lattices (SMILES, Figure 1A), where cationic fluorophores (green) are efficiently isolated from each other by the large disc-shaped anion complexes formed between anions (orange) and two equivalents of cyanostar (grey, Figure 1B), as sketched in Figure 1. [44][45] The SMILES concept has been demonstrated for a range of prevalent dye classes in both thin films and crystals 44 as well as in nanoparticles, [46][47] yielding both very high brightness and high dye density in the solids (up to ~0.5 M, or one dye per 3.5 nm 3 ).…”
Section: Introductionmentioning
confidence: 99%